Painting the Future: Historical Analysis of the Batik Industry and its Impact on the Economy and Islamic Education in Gemekseti Village, Kebumen 1948-1969: Melukis Masa Depan: Analisis Historis terhadap Industri Batik dan Dampaknya terhadap Ekonomi dan Pendidikan Islam Di Desa Gemekseti Kebumen tahun 1948-1969 - Hasanah, Ulfah; Faidi, Ahmad (Nur Science Institute, 2023)
This research examines the history of the batik industry and its impact on the development of Islamic education in Gemeksekti Village, Kebumen District, Kebumen Regency. The method used in this research is the historical method; namely heuristics, criticism, interpretation, and historiography. Historically, the batik industry in Gemeksekti Village has existed and been known since the 19th century as mentioned in the book Batikrapport written by P. De Kat Anggelino in 1930. In the 1960s the batik industry in Gemekseti experienced quite rapid development after receiving support from the Indonesian Batik Cooperative Association (GKBI). This progress also had an impact on the economic welfare of the Gemeksekti Village community. The increasingly improving economic conditions of the Gemekseti community have encouraged several figures and Gemekseti batik entrepreneurs to agree to establish a Compulsory Madrasah Learning (MWB) educational institution and batik entrepreneurs who act as donors. In 1969, due to encouragement from Gemekseti entrepreneurs and the Government on the other hand, this MWB was transformed into the Model State Intidaiyah Madrasah (MIN) in Gemeksekti Village.